A Very Rare Case of Expanded Dengue Syndrome with Acute Liver Failure, Rhabdomyolysis, Acute Kidney Injury and ARDS: Successfully Treated with Haemoadsorption, Hemodialysis, and Plasma Exchange (Bangladesh Critical Care Journal, 2025)
Expanded dengue syndrome, accompanied by liver failure, rhabdomyolysis, acute kidney injury, and severe acute respiratory distress syndrome (ARDS), represents a highly lethal condition with a significantly elevated mortality rate. Conventional treatments are ineffective in addressing all these complications concurrently. This case report discusses a young male patient who underwent haemoadsorption, hemodialysis, and subsequently plasma exchange. The patient achieved full recovery without any residual impairment. This report presents the first instance of a dengue patient undergoing simultaneous haemoadsorption and hemodialysis, followed by plasma exchange.Bangladesh Crit Care J March 2025; 13 (1): 51-55